2014
DOI: 10.1111/pce.12367
|View full text |Cite
|
Sign up to set email alerts
|

Is nitrogen transfer among plants enhanced by contrasting nutrient‐acquisition strategies?

Abstract: Nitrogen (N) transfer among plants has been found where at least one plant can fix N2 . In nutrient-poor soils, where plants with contrasting nutrient-acquisition strategies (without N2 fixation) co-occur, it is unclear if N transfer exists and what promotes it. A novel multi-species microcosm pot experiment was conducted to quantify N transfer between arbuscular mycorrhizal (AM), ectomycorrhizal (EM), dual AM/EM, and non-mycorrhizal cluster-rooted plants in nutrient-poor soils with mycorrhizal mesh barriers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 70 publications
(157 reference statements)
2
34
0
Order By: Relevance
“…However, while liberal movement of N seems to occur in the system observed here (Fig. a) which should help sustaining biodiversity (Teste et al ), it is known that A. longifolia decreases biodiversity during invasion by increasing monospecific plant cover and outcompeting the native vegetation (Marchante et al , Hellmann et al ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, while liberal movement of N seems to occur in the system observed here (Fig. a) which should help sustaining biodiversity (Teste et al ), it is known that A. longifolia decreases biodiversity during invasion by increasing monospecific plant cover and outcompeting the native vegetation (Marchante et al , Hellmann et al ).…”
Section: Discussionmentioning
confidence: 69%
“…a). There is evidence that increased turnover and liberal movement of N between plants could be a mean to decrease competition and increase plant aggregation in a situation where N and P are co‐limiting (Teste et al ). Indeed, Mediterranean dunes are known to be both very N and P limited (Martínez et al ) and extractable P levels of the soil measured here (Table ) were half of those reported earlier for similar systems (Marchante et al ), thus being indicative of severely nutrient‐ deficient soil (Funk ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, however, have demonstrated that the hyphae of AM fungi grow into organic patches of varying complexity and transfer 15 N from these organic patches to their host plant [104,105], and that this can lead to higher plant N contents [106]. When the fungus had access to organic patches that were labelled with 15 N and 13 C, the fungal ERM got only enriched with 15 N, but not with 13 C. This confirms that AM fungi do not have saprophytic capabilities and that the fungus acquires 15 N from these organic patches likely as a decomposition product [105]. However, even if AM fungi themselves do not act as decomposers, AM fungi accelerate the N mineralization from organic matter [107] and affect the carbon flow through soil microbial communities during decomposition [108].…”
Section: Uptake Of Organic N By Hyphaementioning
confidence: 99%
“…These many-to-many interactions allow both partners in the symbiosis to choose among multiple trading partners but also force both partners to compete with other partners for nutrient or carbon resources [12,13]. CMNs play a key role for the long distance transport of nutrients, water, stress chemicals and allelochemicals and allow the interconnected host plants to "communicate" with other plants within their CMN [14][15][16][17][18]. CMNs have also been discussed as a pathway for the transport of N from donor to recipient plants [19].…”
Section: Introductionmentioning
confidence: 99%
“…Legumes increase available nitrogen for companion non‐legumes, potentially via nitrogen sparing (Rasmussen et al ), which could rapidly lead to an autogenically influenced ecosystem. Mycorrhizal networks like those of arbuscular mycorrhizae can lead to a better nitrogen supply for neighboring plants by co‐occurance (He et al ; Teste et al ). Roots of the three investigated species in our study had very low mycorrhizal intensity.…”
Section: Discussionmentioning
confidence: 99%